2017
DOI: 10.1016/j.biocon.2016.12.008
|View full text |Cite
|
Sign up to set email alerts
|

Bumble bee colony growth and reproduction depend on local flower dominance and natural habitat area in the surrounding landscape

Abstract: Conservation measures for bees often focus on increasing the diversity and abundance of floral resources. But it has not been clear if observed benefits of floral enhancements result from greater population growth, which is critical for the long-term success of conservation, or from mobile foragers aggregating in high-resource locations. Experimental evidence is only beginning to emerge in favor of the former mechanism and it is not well-established how different aspects of floral resources affect population g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
45
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 43 publications
(46 citation statements)
references
References 51 publications
1
45
0
Order By: Relevance
“…Furthermore, understanding how disturbance affects both the consumer and resource isotopic signatures can offer insight into the mechanisms by which disturbances affect communities and important ecological functions including seed dispersal and predation, aphid tending, top-down control of insect herbivores, and decomposition and nutrient cycling (Agosti, Majer, Alonso, & Schultz, 2000;Blomqvist, Olff, Blaauw, Bongers, & Putten, 2000;Culver & Beattie, 1980;Dostál, 2005). In our previous work in tallgrass prairies, we document changes in both plant and ant diversity following biomass removal (Kim, Bartel, Wills, Landis, & Gratton, 2018;Kim et al, 2017;Spiesman, Bennett, Isaacs, & Gratton, 2017), in part to due to greater openness and changes in the competitive interactions of ants following the disturbance (Andersen, 2019). These changes in habitat structure and resource availability could also affect the feeding behavior of ants within these grasslands (Kaspari, Donoso, Lucas, Zumbusch, & Kay, 2012).…”
mentioning
confidence: 70%
See 1 more Smart Citation
“…Furthermore, understanding how disturbance affects both the consumer and resource isotopic signatures can offer insight into the mechanisms by which disturbances affect communities and important ecological functions including seed dispersal and predation, aphid tending, top-down control of insect herbivores, and decomposition and nutrient cycling (Agosti, Majer, Alonso, & Schultz, 2000;Blomqvist, Olff, Blaauw, Bongers, & Putten, 2000;Culver & Beattie, 1980;Dostál, 2005). In our previous work in tallgrass prairies, we document changes in both plant and ant diversity following biomass removal (Kim, Bartel, Wills, Landis, & Gratton, 2018;Kim et al, 2017;Spiesman, Bennett, Isaacs, & Gratton, 2017), in part to due to greater openness and changes in the competitive interactions of ants following the disturbance (Andersen, 2019). These changes in habitat structure and resource availability could also affect the feeding behavior of ants within these grasslands (Kaspari, Donoso, Lucas, Zumbusch, & Kay, 2012).…”
mentioning
confidence: 70%
“…We focus on ants as consumer species because they have diverse diets including plant-derived material such as seeds, nectar, and honeydew from sucking insects, and animal-derived materials including herbivores, predators, and microarthropods such as collembola and springtails. In our previous work in tallgrass prairies, we document changes in both plant and ant diversity following biomass removal (Kim, Bartel, Wills, Landis, & Gratton, 2018;Kim et al, 2017;Spiesman, Bennett, Isaacs, & Gratton, 2017), in part to due to greater openness and changes in the competitive interactions of ants following the disturbance (Andersen, 2019). While there are a few studies that have tested whether disturbance affects trophic structure of ants (e.g., Penick, Savage, & Dunn, 2015;Resasco et al, 2012;Woodcock et al, 2013), these studies did not control for site-level differences in isotopic signatures of baseline resources (i.e., plants) which could also vary with disturbance.…”
mentioning
confidence: 99%
“…We hypothesise that this response is due to the presence of similar quantities of alternate floral resources across these landscape with highly different land cover types. Indeed, other studies have also found that woodland cover does not necessarily translate to increased resource abundance (Winfree et al, 2007;Mallinger et al, 2015;Spiesman et al, 2017). Additionally, the quality of resources in the surrounding landscape may have been no different from cranberry, making foraging outside of cranberry during crop bloom uneconomical.…”
Section: Landscape Effectsmentioning
confidence: 98%
“…Data from this study were a part of a larger study examining the effects of biomass harvest on arthropod communities and arthropod-derived ecosystem services (see Kim et al 2017, Spiesman et al 2017. Data from this study were a part of a larger study examining the effects of biomass harvest on arthropod communities and arthropod-derived ecosystem services (see Kim et al 2017, Spiesman et al 2017.…”
Section: Study Systemmentioning
confidence: 99%
“…This study took place in tallgrass prairies in Wisconsin in 2013-2015 in 20 sites. Data from this study were a part of a larger study examining the effects of biomass harvest on arthropod communities and arthropod-derived ecosystem services (see Kim et al 2017, Spiesman et al 2017. Sites were managed by the US Fish and Wildlife Service (N = 13) and Wisconsin Department of Natural Resources (N = 7) and were at least 2 km away from one another.…”
Section: Study Systemmentioning
confidence: 99%